Photovoltaic Thermal Collector System Based On Heterojunction Intrinsic (HIT) Panel - Rosli, Muhammad Nasrul Faiz (Universiti Sains Malaysia, 2018)
In this project, Photovoltaic thermal or PVT system based on heterojunction intrinsic (HIT) panel was designed, built and tested. This system not only produces electricity but it also generates hot water. HIT PV solar panel with the solar thermal collector and without thermal collector will be presented and analysed. The first objective of this project is to design and test a PVT system based on heterojunction intrinsic (HIT) panel. The second objective is to compare the performance of the heterojunction intrinsic (HIT) panel with and without the thermal collector. Microcontroller data acquisition was built to measure and collect data from the system. All the electrical parameter were saved on micro SD card for every 5 minutes using data logger developed using Arduino. The data collected were used to observe the I-V characteristics of HIT panel with and without thermal collector and also the energy output generated from the system. The experiment was conducted for 5 hours to obtain output current, output voltage and maximum output power. From the result analysis, the HIT with thermal collector has improved its performance by 22.64% and lowered the solar panel temperature by 9.49%.